The influence of trainees' characteristics and environmental factors on the effectivess of training - Ismail, Edora; Din, Ghazali (2010)

(untitled)
The study examined the relationship between trainee characteristic and environmental factors with the perception towards transfer of training.The outcomes of the successful training transferability were observer based on the impact on the job performance self-competencies and organizational commitment.A company operated in Malaysia took part in the study. 178 middle managers were selected as sample for the have significant relationship with the perception towards transfer of training. As a whole,each of the dimensions of trainee characteristics was found to have significant relationship with the perceptions towards the transfer of training. The dimensions of trainee characteristics consist of motivational related and ability related variables. The result also revealed that as a whole, environmental factors were found to have significant relationship with the perceptions towards transfer of training. Apart from that one of the dimensions of the environmental factors which is job perceptions towards transfer training.In conclusion the perticipants indicated that the success of training trasferability have positive influence on their job performance, self-competencies and organizational commitment.